Cardio-pulmonary resuscitation challenges in selected Botswana hospitals: Nurse managers' views - Lakshmi Rajeswaran; Valerie J. Ehlers (AOSIS, 2013)
Road traffic accident victims, as well as persons experiencing cardiac and other medical emergencies, might lose their lives due to the non-availability of trained personnel to provide effective cardio-pulmonary resuscitation (CPR) with functional equipment and adequate resources.The objectives of the study were to identify unit managers' perceptions about challenges encountered when performing CPR interventions in the two referral public hospitals in Botswana. These results could be used to recommend more effective CPR strategies for Botswana's hospitals. Interviews, comprising two quantitative sections with closed ended questions and one qualitative section with semi-structured questions, were conducted with 22 unit managers. The quantitative data indicated that all unit managers had at least eight years' nursing experience, and could identify CPR shortcomings in their hospitals. Only one interviewee had never performed CPR. The qualitative data analysis revealed that the hospital units sometimes had too few staff members and did not have fully equipped emergency trolleys and/or equipment. No CPR teams and no CPR policies and guidelines existed. Nurses and doctors reportedly lacked CPR knowledge and skills. No debriefing services were provided after CPR encounters. The participating hospitals should address the following challenges that might affect CPR outcomes: shortages of staff, overpopulation of hospital units, shortcomings of the emergency trolleys and CPR equipment, absence of CPR policies and guidelines, absence of CPR teams, limited CPR competencies of doctors and nurses and the lack of debriefing sessions after CPR attempts.